Analysis of business capital, financial management, and marketing technology on the performance of micro, small, and medium enterprises (MSMEs) in Kotabumi, North Lampung - Hermansyah, Hermansyah; WA, Armalia Reny; Alie, Maria Septijantini; CN, Yudhinanto; Oktaria, Eka Travilta; Megasari, Megasari (Global Academy of Business Studies, 2025)
Purpose: This study examines how business capital, financial management, and marketing technology affect MSME performance in Kotabumi, North Lampung, highlighting their strategic economic role and the challenges they face in sustaining and developing their businesses. Methodology: This research uses a quantitative survey approach by distributing questionnaires to MSME actors. The collected data were analyzed using multiple linear regression to determine the partial and simultaneous effects of business capital, financial management, and marketing technology on MSME performance. Result: The findings indicate that business capital, financial management, and marketing technology positively and significantly influence MSME performance, both partially and simultaneously. This result highlights the essential role of capital accessibility, managerial financial capability, and the effective utilization of marketing technology in enhancing competitiveness and sustainability. Conclusion: The study concludes that strengthening financial resources, improving financial literacy, and optimizing the use of marketing technology are crucial strategies for MSMEs to improve performance and sustain growth. Limitation: The research is limited to MSMEs in Kotabumi, North Lampung, and uses a survey method with a relatively small sample size, which may reduce the generalizability of findings to other regions or contexts. Contribution: This study highlights how capital, financial management, and marketing technology jointly enhance MSME performance, offering valuable insights for policymakers and practitioners to design targeted empowerment strategies that strengthen local economic resilience.